REDUCING OVER-SIZE AND CRACKED TUBERS IN SEED POTATO CROP THROUGH DATES OF HAULM KILLING - Singh, R K; Sharma, Jyotsana; Singh, Sarjeet; Singh, S N (Potato Journal, 2013)
The effect of three haulms killing dates i.e 70, 80 and 90 days after planting on proportion of over-size and cracked tubers in the produce of seed potato crop of Kufri Sutlej was studied. Advancing the haulms killing date by 20 days significantly reduced the undesirable over-size tuber yield and number by 75% and 68.85%, respectively, and cracked tubers by 51.88% and 39.44% on weight and number basis, respectively.